2016
DOI: 10.1161/jaha.116.004289
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total 25‐OH Vitamin D Adds Little Prognostic Value in Patients Undergoing Coronary Catheterization

Abstract: BackgroundVitamin D deficiency is associated with an increased risk of cardiovascular disease; however, it is unclear whether vitamin D status should be considered in clinical risk assessments of patients with cardiovascular disease.Methods and ResultsThis study included 2975 patients who had their first serum total 25‐hydroxy vitamin D (25‐OH vitamin D) measurement before their first coronary catheterization in Alberta, Canada. Cox regression was used to examine associations between 25‐OH vitamin D and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In contrast, no association between vitamin D and mortality was found in a prospective study of older men (32) . Similarly, Gerling et al (33) found that serum total 25-OH vitamin D was inversely associated with mortality risk, and this association was attenuated by several competing risk factors. They suggested that overall 25-OH vitamin D added little prognostic value over established risk factors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, no association between vitamin D and mortality was found in a prospective study of older men (32) . Similarly, Gerling et al (33) found that serum total 25-OH vitamin D was inversely associated with mortality risk, and this association was attenuated by several competing risk factors. They suggested that overall 25-OH vitamin D added little prognostic value over established risk factors.…”
Section: Discussionmentioning
confidence: 89%
“…Vitamin D may attenuate the adverse effects (including increased NFκB expression) of advanced glycation end-products on endothelial cells (42) . A previous study demonstrated that 25(OH)D downregulated tissue factor and up-regulated thrombomodulin expression in cultured monocytic cells via a VDR-mediated mechanism (33) . Last, parathyroid hormone is elevated in patients with VDD.…”
Section: Discussionmentioning
confidence: 98%
“…Researchers found that addition of serum 25(OH)D to the Framingham Risk Score could improve coronary heart disease risk estimation in patients with essential hypertension [25] . However, considering 25(OH)D in addition to established risk factors only marginally added prognostic value of mortality risk in patients undergoing coronary catheterization [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that the addition of serum 25(OH)D to the Framingham Risk Score could improve coronary heart disease risk estimation in patients with essential hypertension or patients with T2D ( 22 , 23 ). However, adding serum 25(OH)D in addition to established risk factors only marginally added prognostic value of mortality risk in patients undergoing coronary catheterization ( 49 ). Considering that vitamin D deficiency and insufficiency are easy to be diagnosed and cured, future studies are needed to evaluate the cost-benefit of adding serum 25(OH)D into the T2D risk estimation and then determine the feasibility of measuring serum 25(OH)D for T2D prevention, especially in high-risk populations.…”
Section: Discussionmentioning
confidence: 99%